Telif Hakkı sözleşmelerine uygulanacak hukuk - Öztürk, Ayşenur (My University, 2018)
Telif hakkı sözleşmesi, eser sahibinin eseri üzerindeki hakları yahut bu hakların kullanımını bir başkasına devretme yükümlülüğü altına girdiği sözleşmedir. Bu sözleşme, eser üzerindeki mali haklara yönelik olup eserin çoğaltılması, yayılması, temsili yahut umuma iletimi gibi konularda yapılabilmektedir. Çalışmamızın amacı, milletlerarası nitelikli telif hakkı sözleşmelerine uygulanacak hukukun tespitini yapmaktadır. Bu tespit yapılırken öncelikle Türk hukuku ve karşılaştırmalı hukukta telif hakkı kavramı ve telif hakkı sözleşmesi incelenmiştir. Takiben sözleşmeye uygulanacak hukukun tespiti yapılmış; Avrupa Birliği hukuku ve Amerika Birleşik Devletleri hukuku ile karşılaştırmalı olarak 5718 sayılı Milletlerarası Özel Hukuk ve Usul Hukuku Hakkında Kanun’un 28. maddesi incelenmiştir.

Copyright agreement is an agreement in which the author enters into obligation of transferring his right on the work or the right of the usage of this work to another person. This agreement is about the financial rights upon the work; thus, can be signed for the issues such as the reproduction, distribution, performance of the work, and its communication to the public. The aim of this study is to identify the law which should be applied to the international copyright agreements. While doing this identification, first of all, the notion of copyright and copyright agreement in the Turkish law and comparative law are examined. Then, applicable law to the agreement is tried to be determined. Article 28 of the Act on Private International and Procedural Law, which is the law numbered 5718, is examined comparatively with the European Union law, the law of the United States of America and the Swiss law.
Keywords: applicable law; Copyright; Cultural property; Fikri haklar; Intellectual property; Kültür varlıkları; Law and legislation; milletlerarası özel hukuk; private international law; Telif hakkı; Telif hakkı sözleşmesi; Turkey; Türkiye; uygulanacak hukuk Copyright agreement; Yasa ve yasama